Formation of development strategy of science intensive industries in Ukraine - Кошевий, Микола Миколайович (Technology audit and production reserves, 2013)
The article concerns the features of the development of the science intensive industries, the need to improve their scientific and technological level and to develop a strategy of the development of the science intensive industries in Ukraine. Therefore, the relevance of the research is identified by the need to develop the strategies of development of the domestic science intensive industries and the mechanism of their management. Despite a large number of scientific improvements on the problems of development and management of science intensive industries it requires further scientific analysis of functioning of science intensive industries to identify approaches of formation of their development strategy. The analysis of the scientific and technological potential of Ukraine, of the financial support of the scientific and technical activities, of the level of science intensity of GDP and industry leads to the formation of the development strategy of science intensive industries, whose main task is to determine the optimal path of their development, the allocation of priorities, etc. Based on the analysis the article outlines the measures of stimulation of the development of the science intensive industries, and the creation of scientific production holdings. Such form of association ensures the stability of the internal control system and close interaction of a company with subsidiaries and affiliated companies. The results can be used to determine the priorities of the innovation development of the sectors of the national economy and industry of Ukraine, as well as to determine the mechanisms for effective functioning and development of science intensive industries.